Crecimiento de juveniles de Calophysus macropterus (Liechtenstein, 1819) “mota” con diferentes tasas de alimentación y tres niveles proteicos cultivado en ambientes controlados - Soplin Guardia, Juan Jesus (2022)
The purpose of the present study was to evaluate the effects of three levels (30, 35 and 40%) of protein and two feeding rates (3 and 6%) and their interactions on growth of juvenile Calophysus macropterus. A total of 144 fish were cultured in tanks for a period of 90 days. Every fifteen days the weight and length of the fish were recorded. Growth in weight and length was determined; likewise, the productive indices: daily weight gain (GPD), weight variation coefficient (CVP), specific growth rate (TCE), apparent feed conversion ratio (ICAA), condition factor (K) and survival (S). The temperature (°C), dissolved oxygen (mg/L), pH (UI) and ammonium (mg/L) of the water in the fish tanks were monitored. The result of the t-student analysis showed that the evaluated feeding rates influenced (p<0.0001) the apparent feed conversion ratio, registering ICAA of 3.54±0.92 (3% rate) and 7.03±0.96 (6% rate). The result of the One-way ANOVA analysis showed that protein levels do not influence (p> 0.05) the growth and productive indices of Calophysus macropterus juveniles. Likewise, there was no significance (p> 0.05) in the interaction of rates and protein levels. Calophysus macropterus juveniles fed under the P40T3 treatment (40% protein and 3% feeding rate) recorded an increase in growth (PF=19.29 ± 0.39 g, GP=12.36 ± 3.44 g, LF= 14.49 ± 0.80 and GL = 3.09 ± 0.05) and productive indices (GPD =0.82 ± 0.23 g/day, CVP =14.22 ± 4.02%, TCE=0.49 ± 0.08) and lower ICAA value (2.87 ± 0.31). The parameters of water quality, temperature, dissolved oxygen and ammonium were within the ranges for the culture of Amazonian fish. In conclusion, only the feeding rate influenced the apparent feed conversion ratio in cultured Calophysus macropterus.